Additive Technologies Application for Increased Cooling Performance in a Megacar Application - Hjalmarsson, Joel; Adrián, Victor Infante (My University, 2025)
This thesis explores the use of additive manufacturing (AM) to improve cooling performance in a mega car. The main objective was to conduct a comprehensive study on the application of 3D printing technologies in the development of heat exchangers. AM has emerged as a powerful tool in this field, enabling the creation of highly efficient complex structures with unprecedented design freedom. The project began with a pre-study aimed at understanding the technology and defining the constraints that influence design, including those related to car development and the company’s context. A parametric model of a baseline heat exchanger (HEX) was created based on tutorials to evaluate the impact of different parameters on performance. The main tools used to carry out the study has been nTopology, CFD simulations in Ansys and AM-specific platforms like Materialise Magics and Simufact Additive. The work has been carried out as a collaboration with Koenigsegg Automotive AB and covers material selection, manufacturing processes, and internal structure design. The findings of the development provided an efficient heat exchanger design, optimized through simulation for performance and production feasibility. Since this technology is still relatively new and limited to a few industries, research and development have been found to be both expensive and time-consuming. A socioeconomic study was conducted to assess these challenges and their impact in society. Despite the complexity and high costs, additive manufacturing was a strong approach for low-volume, high-performance applications, as in the high-performance automotive industry
Keywords: Additive manufacturing (AM); Triply Periodic Minimal Surfaces (TPMS); Lattice; Heat exchanger (HEX); 3D printing; Powder Bed Fusion - Laser Beam (PBF-LB)